GSTP1 rs1138272 Polymorphism Affects Prostate Cancer Risk - Santric, Veljko; Djokic, Milica; Suvakov, Sonja; Pljesa-Ercegovac, Marija; Nikitovic, Marina; Radic, Tanja; Acimovic, Miodrag; Stankovic, Vesna; Bumbasirevic, Uros; Milojevic, Bogomir; Babic, Uros; Dzamic, Zoran; et al. (Medicina (Kaunas, Lithuania), 2020)
Background and Objectives: One of the most frequent genetic alterations reported to date in prostate cancer (PC) is aberrant methylation of glutathione transferase P1 (GSTP1). Taking into consideration the involvement of oxidative stress in PC pathogenesis and recent advances in scientific understanding of the role of GSTP1*Ala114Val rs1138272 polymorphism in carcinogenesis, we hypothesized that this single-nucleotide polymorphism (SNP) influences the risk of PC independently of, or in combination with, other GST polymorphisms, including GSTP1*IIe105Val rs1695 or GSTM1 and GSTT1 deletion polymorphisms. Materials and Methods: Genotyping was performed in 237 PC cases and in 236 age-matched controls by multiplex polymerase chain reaction (PCR) for deletion of GST polymorphisms and by quantitative PCR for SNPs. Results: We found that carriers of either GSTP1*Val (rs1138272) or GSTP1*Val (rs1695) variant alleles had a PC risk compared to individuals with both referent alleles (OR = 4.93, 95%CI: 2.89–8.40, p < 0.001 and OR = 1.8, 95%CI: 1.19–2.73, p = 0.006, respectively). Additionally, in a haplotype analysis we found that individuals with GSTP1*C haplotype, represented by both variant alleles (GSTP1*Val rs1695 + GSTP1*Val rs1138272), had a 5.46 times higher risk of PC development compared to individuals with the most frequent haplotype (95%CI = 2.56–11.65, p < 0.001), suggesting a potential role of those variants in PC susceptibility. A regression analysis on the number of risk-associated alleles per individual (GSTM1*active, GSTT1*null, GSTP1*Val rs1695 and GSTP1*Val rs1138272) showed a significant increase in the risk of developing PC, from 3.65-fold in carriers of two risk alleles (95%CI = 1.55–8.61, p = 0.003) to an approximately 12-fold increase in carriers of all four risk alleles (95%CI = 3.05–44.93, p < 0.001). Conclusion: Prostate cancer may be influenced by multiple glutathione transferase (GST) polymorphic genes, especially GSTP1, highlighting the role of gene–gene interactions in human susceptibility to this cancer.